Exploring the long-term sequelae of childhood sexual abuse on risky sexual behavior among Chinese transgender women - Chen, Yingjie; Chang, Ruijie; Hu, Fan; Xu, Chen; Yu, Xiaoyue; Liu, Shangbin; Xia, Danni; Chen, Hui; Wang, Rongxi; Liu, Yujie; Ge, Xin; Ma, Tiecheng; et al. (Frontiers in Psychology, 2023)
Introduction: Childhood sexual abuse (CSA) is a hidden but serious public health issue that can lead to a series of behavioral consequences and health problems in adulthood. It has been well documented that transgender women (TGW) have a high prevalence of CSA victimization. Moreover, risky sexual behaviors are also widespread among TGW; nevertheless, research investigating the associations between CSA victimization and risky sexual behaviors in TGW represents a gap in the literature. Methods: Our research was carried out mainly in Shenyang of China from November 2018 to January 2019. Sociodemographic characteristics, as well as information on participants' HIV awareness and sexual behaviors, were collected through face-to-face interviews. The impact of CSA was examined through hierarchical logistic regression, adjusted for sociodemographic factors and HIV awareness. Results: In the sample of 247 adult TGW, 14.2% of them had CSA history. In the previous six months, 30.8% of the participants reported condomless anal intercourse (CAI) and 38.5% of them had multiple sexual partners (MSP). The findings demonstrated that TGW with CSA history were more likely to take part in CAI (P=0.001, OR=4.252) or have MSP (P=0.004, OR=3.260) in adulthood. Further, HIV knowledge was not a predictor of CAI or MSP, but higher HIV risk perception was associated with greater probability of CAI. Conclusion: TGW with a history of CSA were more prone to engage in CAI and have MSP in mainland China.